Stereoisomers of Saponins in Panax notoginseng (Sanqi): A Review - Peng, Ming; Yi, Ya X.; Zhang, Tong; Ding, Yue; Le, Jian (Frontiers in Pharmacology, 2018)
Panax notoginseng (Sanqi), a traditional Chinese medicine which has been applied to medical use for over four centuries, contains high content of dammarane-type tetracyclic triterpenoid saponins. A number of stereoisomeric dammarane-type saponins exist in this precious herb, and some are particularly regarded as “biomarkers” in processed notoginseng. Contemporary researches have indicated that some saponin stereoisomers may show stereospecific pharmacological activities, such as anti-tumor, antioxidative, anti-photoaging, anti-inflammatory, antidiabetic, and neuro-protective activities, as well as stereoselective effects on ion channel current regulation, cardiovascular system, and immune system. The current review provides a comprehensive overview of chemical compositions of raw and processed P. notoginseng with a particular emphasis on saponin stereoisomers. Besides, the pharmacological and pharmacokinetic researches, as well as determination, biotechnological isolation and preparation methods of stereoisomeric saponins in notoginseng are discussed extensively.